ROHANA KUDUS DAN PENDIDIKAN PEREMPUAN - Silfia Hanani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Rohana Kudus is a woman combatant from Minangkabau. She never went to school and only learning by self-educatedly. Even though, her struggle in education have started since childhood. She struggled for the woman education until she died. She struggeled not only through the education instituation but also through the newspaper. The act of Rohana in woman education can be seen trought the founding of Kerajinan Amai Setiia School in Koto Gadang Bukittinggi. In journalist, Rohana is noted as the first journalist woman in Indonesia and founded the newspaper for woman in her home town. She ever invited by the Dutch governance to came to Amstardam, but it was rejected, because she was not able to fight against the cultural construrction which did not permit woman to be active in polict. Finally, Rohana decided to remain her struggle for woman tthrough the journalist and education until she died.